On the evaluation of edgeless diode detectors for patient-specific QA in high-dose stereotactic radiosurgery. (September 2021) - De Martin, Elena; Alhujaili, Sultan; Fumagalli, Maria Luisa; Ghielmetti, Francesco; Marchetti, Marcello; Gallo, Pasqualina; Aquino, Domenico; Padelli, Francesco; Davis, Jeremy; Alnaghy, Saree; Carrara, Mauro; Fariselli, Laura; et al.
Graphical abstract: Highlights: Radiosurgery is a powerful tool in the treatment of a wide spectrum of conditions. There is a lack of efficient equipment for radiosurgery patient-specific QA programs. Brain functional treatments condense all the criticalities of radiosurgery dosimetry. Edgeless diodes are angular independent and measure brain functional treatment dose. The edgeless diode is an efficient dosimeter for patient-specific QA in radiosurgery. Abstract: Purpose: In this work, the potential of an innovative "edgeless" silicon diode was evaluated as a response to the still unmet need of a reliable tool for plan dosimetry verification of very high dose, non-coplanar, patient-specific radiosurgery treatments. In order to prove the effectiveness of the proposed technology, we focused on radiosurgical treatments for functional disease like tremor or pain. Methods: The edgeless diodes response has been validated with respect to clinical practice standard detectors by reproducing the reference dosimetry data adopted for the Treatment Planning System. In order to evaluate the potential for radiosurgery patient-specific treatment plan verification, the anthropomorphic phantom Alderson RANDO has been adopted along with three edgeless sensors, one placed in the centre of the Planning Target Volume, one superiorly and one inferiorly. Results: The reference dosimetry data obtained from the edgeless detectors are within 2.6% for output factor, off-axis ratio and well within 2% for tissue phantom ratio when compared to PTW 60, 018 diode. The edgeless detectors measure a dose discrepancy of approximately 3.6% from the mean value calculated by the TPS. Larger discrepancies are obtained in very steep gradient dose regions when the sensors are placed outside the PTV. Conclusions: The angular independent edgeless diode is proposed as an innovative dosimeter for patient quality assurance of brain functional disorders and other radiosurgery treatments. The comparison of the diode measurements with TPS calculations confirms that edgeless diodes are suitable candidates for patient-specific dosimetric verification in very high dose ranges delivered by non-isocentric stereotactic radiosurgery modalities.